Features of SARS-CoV-2 Replication in Various Types of Reptilian and Fish Cell Cultures - Yulia Kononova; Lyubov Adamenko; Evgeniya Kazachkova; Mariya Solomatina; Svetlana Romanenko; Anastasia Proskuryakova; Yaroslav Utkin; Marina Gulyaeva; Anastasia Spirina; Elena Kazachinskaia; Natalia Palyanova; Oksana Mishchenko; et al. (Viruses, 2023)
Background: SARS-CoV-2 can enter the environment from the feces of COVID-19 patients and virus carriers through untreated sewage. The virus has shown the ability to adapt to a wide range of hosts, so the question of the possible involvement of aquafauna and animals of coastal ecosystems in maintaining its circulation remains open. Methods: the aim of this work was to study the tropism of SARS-CoV-2 for cells of freshwater fish and reptiles, including those associated with aquatic and coastal ecosystems, and the effect of ambient temperature on this process. In a continuous cell culture FHM (fathead minnow) and diploid fibroblasts CGIB (silver carp), SARS-CoV-2 replication was not maintained at either 25 °C or 29 °C. At 29 °C, the continuous cell culture TH-1 (eastern box turtle) showed high susceptibility to SARS-CoV-2, comparable to Vero E6 (development of virus-induced cytopathic effect (CPE) and an infectious titer of 7.5 ± 0.17 log10 TCID50/mL on day 3 after infection), and primary fibroblasts CNI (Nile crocodile embryo) showed moderate susceptibility (no CPE, infectious titer 4.52 ± 0.14 log10 TCID50/mL on day 5 after infection). At 25 °C, SARS-CoV-2 infection did not develop in TH-1 and CNI. Conclusions: our results show the ability of SARS-CoV-2 to effectively replicate without adaptation in the cells of certain reptile species when the ambient temperature rises.